Efektivitas Role Playing terhadap Keterampilan Berbicara Bahasa Arab sebagai Alat Evaluasi - Arini Hidayati; Miatin Rachmawati (Jurnal Internasional Pendidikan Bahasa Arab, 2025)
Arabic language learning in schools tends to focus on teaching from the teacher, so this reduces the potential for students to actively participate and engage in discussions that can deepen their understanding of the material being taught. This study aims to see an increase in the mastery of Arabic vocabulary of class X high school students. This study used an experimental quantitative approach with Cluster sampling technique. Data were collected through observation and test. Data presentation was done by validity test, normality test, homogeneity test, t-test, and n-gain test. The experimental class posttest n-gain results showed a value of 70.4% which was in the moderately effective category or moderate criteria. So it can be concluded that the use of role play models in Arabic language learning can improve mastery of Arabic vocabulary. For future research, it is suggested that researchers develop more objective evaluation methods, as well as design role plays that are more inclusive and consider students' emotional comfort. In addition, allocating time effectively and ensuring equal participation can increase the effectiveness of this method in learning.